The pro-fibrogenic role of SPP1+ macrophages in medical implant fibrosis: mechanisms and therapeutic opportunities - Yu, Mei; Fu, Jiayin (Frontiers in Immunology, 2026)
Fibrosis is a major cause of biomedical device failure. Recent advances identify SPP1+ macrophages as pivotal regulators of this process. These cells derive from CCR2+ monocytes, adopt a lipid-associated macrophage-like phenotype, and terminally differentiate within collagen-rich niches at implant interfaces. Spatiotemporal analysis reveals their recruitment via the CCL2-CCR2 axis, persistence in chronic phases (>4 weeks), and spatial co-localization with activated fibroblasts at fibrotic fronts. Through osteopontin-CD44 signaling, they drive fibroblast-to-myofibroblast differentiation and pathological extracellular matrix deposition. Building on this mechanistic insight, emerging therapeutic strategies specifically targeting SPP1+ macrophages, such as blockade of the CCL2-CCR2 axis, inhibition of osteopontin-CD44 signaling, CRISPR-Cas13-based gene circuits, engineered CAR macrophages, and smart biomaterial-based drug delivery systems, hold great promise for mitigating implant-associated fibrosis. A comprehensive understanding of the role of SPP1+ macrophages, coupled with these novel interventions, is crucial for developing precise antifibrotic therapies to maintain the long-term functionality of medical implants.